Bringing the Laboratory Home: PANDABox Telehealth-Based Assessment of Neurodevelopmental Risk in Children - Kelleher, Bridgette L.; Halligan, Taylor; Witthuhn, Nicole; Neo, Wei Siong; Hamrick, Lisa; Abbeduto, Leonard (Frontiers in Psychology, 2020)
Background. Advances in clinical trials have revealed a pressing need for outcome measures appropriate for children with neurogenetic syndromes. However, the field lacks a standardized, flexible protocol for collecting laboratory-grade experimental data remotely. To address this challenge, we developed PANDABox (Parent-Administered Neurodevelopmental Assessment), a caregiver-facilitated, remotely administered assessment protocol for collecting integrated and high quality clinical, behavioral, and spectral data relevant to a wide array of research questions. Here, we describe PANDABox development and report preliminary data regarding: (1) logistics and cost, (2) caregiver fidelity and satisfaction, and (3) data quality. Methods. We administered PANDABox to a cohort of 16 geographically diverse caregivers and their infants with Down syndrome. Tasks assessed attention, language, motor, and atypical behaviors. Behavioral and physiological data were synchronized and coded offline by trained research assistants. Results. PANDABox required low resources to administer and was well received by families, with high caregiver fidelity (94%) and infant engagement (91%), as well as high caregiver-reported satisfaction (97% positive). Missing data rates were low for video frames (3%) and vocalization recordings (6%) but were higher for heart rate (25% fully missing, 13% partially missing) and discrete behavioral presses (8% technical issues; 19% not enough codable behavior), reflecting the increased technical demands for these activities. Conclusions. With further development, low-cost laboratory-grade research protocols may be remotely administered by caregivers in the family home, opening a new frontier for cost-efficient, scalable assessment studies for children with neurogenetic syndromes other neurodevelopmental disorders.